Urinary Incontinence: Its Assessment and Relationship to Depression among Community-Dwelling Multiethnic Older Women - Luciana Laganà; David William Bloom; Andrew Ainsworth (The Scientific World Journal)
Urinary Incontinence (UI) affects many older adults. Some of its deleterious consequences include stress, major depression, diminished quality of life, sexual dysfunction, and familial discord. Of the various mental health problems identified in the literature as being comorbid with UI, the most notable one continues to be depression. Despite a wealth of research contributions on this topic, the available literature is underrepresentative of ethnic minority older women. Culture has been shown to have a significant impact on a woman’s perception of her own UI symptoms; this demonstrates the necessity for the recruitment of ethnically and culturally diverse samples when studying UI. In the present study, we determined the prevalence of UI among 140 community-dwelling, ethnically diverse older women (28.2%), discovered that our new UI screener is reliable, and did not find the UI-depression link to be significant. The clinical and research implications of our findings are discussed.